Effect of the Orientation Difference on Components of Visual Event-Related Potentials - Dushanova, J.; Mitov, D. (Нейрофизиология, 2013)
Changes in the components of visual event-related potentials (VERPs) depending on the difficulty of the identification counting tasks (“coarse” and “fine”) were studied in healthy humans. The basic finding is that much greater changes in the VERPs waves were observed within a 5 to 15 deg range than those within the range of 15 to 90 deg. The amplitude of the second sensory component (P2), the latencies of both sensory components, and that of the second cognitive one increased with increase in the task difficulty, while the amplitudes of both cognitive components N2/P3 decreased. Additionally, small changes in the task difficulty affected the attentional effort and modulated the N1 amplitude and P2 latency. These VERP changes are considered an electrophysiological correlate of the psychophysical data when the “label” of an activated orientation-selective channel is sufficient for “coarse” discrimination, and an additional computational process comparing the responses of the activated channels makes discrimination possible in “fine” discrimination.